Thiol-reducing agents abate cholestasis-induced lung inflammation, oxidative stress, and histopathological alterations - Hossein Niknahad; Ali Nadgaran; Sepideh Alidaee; Abdollah Arjmand; Narges Abdoli; Sahra Mazloomi; Alireza Akhlagh; Ahmad Nikoozadeh; Seyed Mohammad Amin Kashani; Pooria Sayar Mehrabani; Mohammad Rezaei; Mohsen Saeed; et al. (Shiraz University of Medical Sciences, 2023)
Cholestasis is not only influences the hepatic function but also damages many other organs. Lung injury is a critical secondary organ damage associated with cholestasis/cirrhosis. Pulmonary histopathological alterations, respiratory distress, and hypoxia are related to cholestasis/cirrhosis-induced lung injury. It has been found that oxidative stress plays a crucial role in this complication. The current study was designed to investigate the effect of N-acetyl cysteine (NAC) and dithiothreitol (DTT) as thiol-reducing and antioxidant agents against cholestasis-induced lung injury. Bile duct ligated (BDL) rats were monitored for the presence of inflammatory cells, TNF-α, and IgG levels in their broncho-alveolar fluid (BALF) at scheduled time intervals (3, 7, 14, and 28 days post-BDL surgery). These markers reached their highest level in the BALF of BDL rats on day 28 after the surgery. Therefore, in another set of experiments, the BDL animals were treated with NAC (100 and 300 mg/kg/day, i.p, for 28 consecutive days) and DTT (10 and 20 mg/kg/day, i.p, for 28 consecutive days). Meanwhile, a significant increase in the levels of TNF-α and IgG was detected in the BALF of BDL rats. The BALF level of neutrophils, monocytes, and lymphocytes was also significantly increased in cholestatic animals. A significant increase in lung tissue biomarkers of oxidative stress was detected in the BDL rats. It was found that NAC and DTT could significantly blunt pulmonary damage induced by cholestasis. The effects of these agents on oxidative stress biomarkers and inflammatory response seem to play a pivotal role in their mechanisms of protective properties.